Optimization of arabinogalactan and taxifolin extraction process from Dahurian larch (Larix gmelinii) and evaluation of the effects on activities of α‐amylase, α‐glycosidase, and pancreatic lipase in vitro. Issue 5 (23rd July 2018) - Liu, Zaizhi; Wei, Mengxia; Cui, Guoqiang; Yang, Xinyu; Gu, Huiyan; Yang, Lei
Abstract: Double experimental designs, Plackett–Burman design coupled with Box–Behnken design, were used to optimize the simultaneous extraction process of arabinogalactan and taxifolin from Larix gmelinii by ultrasonic microwave synergistic extraction (UMSE) method. The optimal extraction conditions were determined with the extraction yields of 223.40 ± 7.82 mg/g for larch arabinogalactan and 125.02 ± 5.30 mg/g for taxifolin. Compared to conventional methods, UMSE method showed the merits of higher extraction efficiency, saving time, and energy. The molar ratio of galactose to arabinose is found to be 6:1 through the monosaccharide composition analysis of larch arabinogalactan. The obtained taxifolin structure was identified by mass spectrometry, Fourier transform infrared spectroscopy, and nuclear magnetic resonance. Interestingly, larch arabinogalactan and taxifolin showed completely opposite influences on α‐amylase, α‐glycosidase, and pancreatic lipase; it was inferred that larch arabinogalactan could act as an inhibitor while taxifolin as an accelerator. Practical applications In this study, response surface methodology of Plackett–Burman design and Box–Behnken design performed well to obtain the optimal conditions and satisfactory extraction yields for the extraction of arabinogalactan and taxifolin from Larix gmelinii by ultrasonic microwave synergistic extraction method, which could be a good paradigm for the efficient isolation of bioactive substances from plant matrix in the field of separation science. Meanwhile, the results from the evaluation of the effects of two target compounds on activities of α‐amylase, α‐glycosidase, and pancreatic lipase in vitro revealed that larch arabinogalactan and taxifolin enjoyed the completely opposite influences on the three digestive enzymes, namely larch arabinogalactan could act as an inhibitor while taxifolin an accelerator. These results will facilitate the application of larch arabinogalactan and taxifolin in the food and pharmaceutical industries.